Resolusi Konflik Perspektif Pesantren, Studi Pesantren di Bali - Haya, Haya (MANAGIERE: Journal of Islamic Educational Management, 2022)
This research examines the conflict phenomenon between pesantren and the community in Bali which is focused on the leadership of the Kiai. Kiai develops Islam through pesantren. The leadership of the Kiai has strategic aspects in the life of the nation and state. They set conflict resolution with Istiqlal Islamic Boarding School, Buleleng, and the Bali Bina Insani Islamic Boarding School, Tabanan. The theme is a new discourse related to the development of pesantren traditions and values ​​in the discipline of Islamic education management. The leadership of Kiai in Bali is in line with Islamic values. They ​​accomplish the conflict resolution to bring peace to Bali. They actualize it through Islamic boarding schools. Islam means safe and peaceful. The teachings of Islam guide humans on how to get a harmonious and peaceful life. These values ​​become the buffer of human values. Rasulullah SAW taught his followers to spread greetings. The order indicates the existence of Muslims as agents of peace (Ufs al-salam).